2012
DOI: 10.1152/jn.00992.2011
|View full text |Cite
|
Sign up to set email alerts
|

A test of spatial temporal decoding mechanisms in the superior colliculus

Abstract: Katnani HA, Van Opstal AJ, Gandhi NJ. A test of spatial temporal decoding mechanisms in the superior colliculus. J Neurophysiol 107: 2442-2452, 2012. First published January 25, 2012 doi:10.1152/jn.00992.2011.-Population coding is a ubiquitous principle in the nervous system for the proper control of motor behavior. A significant amount of research is dedicated to studying population activity in the superior colliculus (SC) to investigate the motor control of saccadic eye movements. Vector summation with satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…1990). However, previous studies have demonstrated that suboptimal microstimulation can attenuate both kinematics and metrics (Groh 2011;Katnani et al 2012;Stanford et al 1996;Van Opstal et al 1990); moreover, our current study provides a systematic investigation of the differential effects of current intensity and frequency on movement-evoked properties. In this section, we explain our results by speculating on the spatiotemporal features of the overall activity produced during microstimulation.…”
Section: Neural Mechanisms Of Actionmentioning
confidence: 90%
See 1 more Smart Citation
“…1990). However, previous studies have demonstrated that suboptimal microstimulation can attenuate both kinematics and metrics (Groh 2011;Katnani et al 2012;Stanford et al 1996;Van Opstal et al 1990); moreover, our current study provides a systematic investigation of the differential effects of current intensity and frequency on movement-evoked properties. In this section, we explain our results by speculating on the spatiotemporal features of the overall activity produced during microstimulation.…”
Section: Neural Mechanisms Of Actionmentioning
confidence: 90%
“…Data of this nature can be beneficial when designing an experiment to test specific properties of a neural system or to test the predictions of a neural model. For example, within the oculomotor field, the input to output relationship characterized in this investigation provides a resource to challenge existing concepts and models that describe spatiotemporal motor decoding in the superior colliculus (Groh 2001;Katnani et al 2012). In addition, a well-developed neural field model of the collicular network trained on these microstimulation results could reveal emerging properties in the SC and provide insightful information on the mechanisms underlying saccade generation.…”
Section: Significance In the Scientific Settingmentioning
confidence: 99%
“…The vector summation with saturation (VSS) model proposes that the cumulative sum of the collicular output drives the BG until saturation constrains the sum and terminates the movement [23], [37], [38]. We recently concluded that the saturation function could be implemented in multiple ways, including intracollicular interactions and gating by the OPNs [13]. The blink manipulation in the present study explored this latter potential mechanism.…”
Section: Discussionmentioning
confidence: 88%
“…Behavioral paradigms as well as stimulation and reflex-blink procedures were similar to those described in previous papers [8], [12], [13]. Briefly, all animals were trained to perform the oculomotor gap task.…”
Section: Methodsmentioning
confidence: 99%
“…particular their adaptive time constants and lateral-interaction weightings specified by Eqns. [16][17]707 caused the peak firing rates of the cells to drop systematically along the rostral-to-caudal axis, while 708 keeping the total number of spikes constant (Fig. 5).…”
Section: Including Lateral Interactions 542 543mentioning
confidence: 99%